THE IMPLEMENTATION OF MOSQUE-BASED UKHUWAHTUL ISLAMIC DAKWAH PROGRAM IN DESA PANCIRO KECAMATAN BAJENG KABUPATEN GOWA - St. Nasriah; Muliaty Amin; Nurhidayat Muhammad Said; Arifuddin Tike (Jurnal Diskursus Islam, 2022)
This study discusses the implementation of a mosque-based ukhuwahtul Islamiyah da’wah program in Desa Panciro, Kecamatan Bajeng, Kabupaten Gowa. This type of research is field research located in Desa Panciro Kecamatan Bajeng Kabupaten Gowa Provinsi Sulawesi Selatan; the center of the research location is at UkhuwahaI-Islamiyah Mosque, Desa Panciro Kecamatan Bajeng. The approach used is a dakwah science approach, a phenomenological approach, a sociological approach, and a normative theological approach using data collection methods through observation, interviews, literature, and documentation. Descriptive methods carried out the data processing techniques and data analysis. The results showed that the form of dakwah at Lembaga Dakwah Ukhuwatul Islamiyah (LDUI) was Islamic tabligs, Islamic irsyad, Islamic tadbir, Islamic tatwir, and futuhat dakwah by sending dai to remote areas. The context of LDUI dakwah is starting from dawkah nafsiyah, fardiyah, fi’ahqalila and hisbiyah. Furthermore, the researchers found one thing that was different from other dakwah institutions: the existence of dai cadres at LDUI who routinely held dai training every year for six months. There are three stages of that training: the first two months of providing material, the next two months the stage of discussion and deepening, and The last two months of practice and exams, which are closed with graduation.